Hubungan Koordinasi Mata-Kaki Keterampilan Passing Futsal Pada Atlet Futsal Di SMAN 4 Rejang Lebong - M. Aldy Mazak Termizi (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the relationship between foot-eye coordination and futsal passing skills in futsal athletes in Rejang Lebong Regency. This study is a correlational study. The study population was 67 futsal athletes in Rejang Lebong Regency. The sampling technique used purposive sampling, with the criteria (athletes were still actively training at the club, willing to be samples, and not in a state of illness. Based on these criteria, 58 athletes fulfilled the criteria. The foot-eye coordination instrument was measured using the Soccer Wall Volley Test, and basic futsal passing skills included passing. Data analysis used multiple regression. The results showed that there was a significant relationship between foot-eye coordination and futsal passing skills of futsal athletes in Rejang Lebong Regency, with a calculated t-value of -4.742 > t-table 2.004, a p-value of 0.000 <0.05, and a contribution of 35.95%. Conclusion There is a significant relationship between foot-eye coordination and passing.